A REVIEW: THE RISK OF IRON DEFICIENCY WITHIN INFANTS WHO ARE EXCLUSIVELY BREAST FED FOR THE FIRST SIX MONTHS: CASES IN DEVELOPED COUNTRIES - Cholidah, Rifana (Jurnal Kedokteran, 2013)
This review aims to discuss about the risk of iron deficiency within infants who are exclusively breast fed for the first six months after birth, especially in developed countries. It is well documented that iron deficiency is one of the most common nutritional disease among babies and young children. This commonly occurs during an increased need of iron supply particularly in the first period of life. The WHO and many health authorities recommend to exclusively breast fed babies for the first six months of their life for the best achievement on growth, health and development, and no adverse outcome on growth have been reported for breastfeeding babies exclusively for six months. However, a lower level of iron has been identified in some developing country settings.There have been few studies specifically to examine the relationship between infants who are exclusively breast fed for the first six months after birth and the prevalence of iron deficiency in developed countries. Based on the evidence, there are several factors may affect iron stores depletion of babies and toddlers such as dietary intake, socioeconomic, low iron concentration of weaning foods, cowÃ¢â‚¬Å¸s milk consumption and prolonged duration of breastfeeding. Most studies that have been carried out have concluded that there is little risk of iron deficiency and iron deficiency anaemia in infants who are exclusively breast fed for the first six months after birth. It seems that only infants with unusual low iron stores at birth are at risk of deficiency if breast fed exclusively for six months.